(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article deals with the concept of creativity and features of its manifestation in the student age. The article describes the main active teaching methods and reveals their potential in terms of developing students ’ creativity. We also present data from an experimental study that shows the possibility of using active methods to develop certain parameters of creativity